Promoting holistic child development: a collaborative school health approach. - Haynes, N.M. (The Journal of school health, 1998)
3 citations (Crossref) [2023-10-31]
Keywords: *Child Development; *Health Promotion/og [Organization & Administration]; *Holistic Health; *School Health Services/og [Organization & Administration]; Adolescent; Child; Child Development; Cooperative Behavior; Faculty; Health Promotion; Health Services Needs and Demand; Holistic Health; Humans; School Health Services; Social Support; United States; adolescent; child; child development; cooperation; dept.csp; health promotion; health service; human; organization and management; philosophy; review; school health service; social support; university

Research and Program Evaluation - Haynes, N.M.; Gregory, J.L.; Diffley, W.J. (Educational Leadership: Perspectives on Preparation and Practice, 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedag...
Keywords: dept.edl